<span>3-2(Cosx)^2 - 3Sinx = 0.
Recall (Sinx)^2 + (Cosx)^2 = 1.
Therefore (Cosx)^2 = 1 - (Sinx)^2
Substitute this into the question above.
</span><span>3-2(Cosx)^2 - 3Sinx = 0
3 - 2(1 - (Sinx)^2) - 3Sinx = 0 Expand
3 - 2 + 2(Sinx)^2 - </span><span><span>3Sinx = 0</span>
1 + 2(</span><span>Sinx)^2 - 3Sinx = 0 Rearrange
2(Sinx)^2 </span><span><span>- 3Sinx + </span>1 = 0
Let p = Sinx
2p^2 - 3p + 1 = 0 Factorise the quadratic expression
2p^2 - p - 2p +1 = 0
p(2p -1) - 1(2p -1) = 0
(2p-1)(p -1) = 0
Therefore 2p-1=0 or (p-1) = 0
2p=0+1 or (p-1) = 0
2p=1 or p = 0 +1.
p=1/2 or p = 1 Recall p = Sinx
Therefore Sinx = 1/2 or 1.
For 0<u><</u>x<u><</u>360
Sinx =1/2, x = Sin inverse (1/2) , x = 30,
(180-30)- 2nd Quadrant = 150 deg
Sinx = 1, x = Sin inverse (1) , x = 90
Therefore x = 30,90 & 150 degrees.
Cheers.</span>
21 is the answer i think idk try dividing them all or finindng something or look up how to find a standard deviation
Hello!
Let's write this as an equation below.
3x+4=16
We subtract 4 from both sides.
3x=12
Divide both sides by 3
x=4
I hope this helps!
ωєℓℓ αℓℓ уσυ нανє тσ ∂σ ιѕ ∂ινι∂є 1,568 ву 28
ωнι¢н ωιℓℓ єqυαℓ тнє ωαℓℓ тσ вє 56 fєєт.
ι нσρє ι ¢συℓ∂ нєℓρ уσυ
Answer:
g=7.5
Step-by-step explanation:
2/3g=45
divide both sides by 2/3
g=7.5
or
g=7 1/2